Manila, 1645 - Luengo, Pedro 1984- (New York London Routledge, Taylor & Franics Group, 2021)
"Manila, 1645 reconstructs what the city of Manila was like before the earthquakes of the mid-seventeenth century. The book demonstrates the importance of addressing the history of Southeast Asia as a multi-layered framework, rather than a series of entangled histories. In doing so, Manila is contextualized not merely as a Spanish settlement connected to New Spain via America, but instead within Southeast Asia, situated between the Chinese and the Sulú Seas, and located in the centre of commercial routes used by Armenian, Dutch, and Portuguese traders. This historical and geographical context is crucial to understanding later cultural dialogues. Urban planning, housing and architecture, and social networks in the city are also examined. This book will appeal to scholars and students interested in early modern history, global history, and architectural history"--
Manila-Macao: the final jewel in the Iberian global crown -- A big puzzle: urban planning of old Intramuros -- Portraits in wood and stone: houses and society -- Cross-cultural dialogue: adapting a mediterranean house to the Tropic.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (Site, viewed (05/07/21).
Keywords: Architecture, Domestic -- Philippines -- Manila -- History -- 17th century; City planning -- Philippines -- Manila -- History -- 17th century; Intramuros (Manila, Philippines) -- History; Manila (Philippines) -- Civilization -- 17th century